The effect of competency and religiosity values on audit quality with auditor time budget as a moderation (case study at the inspectorate Pringsewu District) - Monica Nadia Sari; Andi Mulyono (Indonesia Accounting Research Journal, 2025)
This research is based on the persistent and high prevalence of corruption, despite the implementation of various eradication measures. This situation indicates significant challenges in detection and prevention. The government sector is the most vulnerable, given the frequent involvement of state officials and corporations in corrupt practices. This fact emphasizes the urgency of developing proactive detection methods, in line with increasing public demand for financial transparency in the government sector. To achieve this, strengthening internal control systems and reliable oversight functions is necessary. Audit quality plays a crucial role as an indicator of the success of regional development, as auditors are tasked with providing relevant information that forms the basis for decision-making. This study used a quantitative approach and included everyone in the population as part of the sample. There were 42 auditors involved in the study. The main information came from questionnaires that were distributed. The data was then analyzed using multiple linear regression, which was performed with SPSS version 23. The study found that both competence and religiosity had a strong positive impact on the quality of audits. It also showed that time pressure helped competent auditors work better and more accurately. However, when time pressure was combined with religiosity, it had a negative effect. This means that tight deadlines can prevent religious values from helping as much as they could in improving audit quality.